JAKET MULTIFUNGSI âVICTORYâS BAGâ (BARANG BEKAS KAYA KREATIVITAS) - Saputra, Herwiyanda Surya; Verrysaputro, Exwan Andriyan; Wibowo, Wisnu Broto; Pujiono, Tomi (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
This entrepreneurship field-Student Creativity Program aims to create designs and to produce a multifunctional Jacket